Job And Life Satisfactions: A Causal Analysis Of Their Relationships - Chacko, Thomas I. (Academy of Management Journal, 1983)
The article discusses the nature of the relationship between work and nonwork satisfactions. It employs longitudinal data to overcome some of the inaccuracies of the earlier studies. The literature concerned with the functional or causal relationship between work and life, nonwork, satisfactions gives inconsistent results. The study used information from two surveys that dealt with the quality of employment as well as overall satisfaction with life. These surveys were given in 1973 and 1977 and investigated 33 different satisfaction facets. The authors conclude that job satisfaction has a greater influence on life satisfaction than life satisfaction has on job satisfaction. Different aspects of employment are analyzed as to how they affect overall life satisfaction.